A genomic exploration of 15 autosomal STR loci for establishment of a DNA profile database of the population of Himachal Pradesh. (September 2020) - Mohapatra, B.K.; Chauhan, Kamal; Shrivastava, Pankaj; Dixit, Shivani; Kumawat, R.K.; Sharma, Anchal; Dagar, Seema; Chaubey, Gyaneshwer
Highlights: This study reports 259 unrelated individuals from the population of Himachal Pradesh. The locus D2S1338 was most polymorphic, and TPOX was the least polymorphic. This genetic data will enrich the DNA databank for forensic applications. Abstract: In order to create an autosomal STR loci population database for Himachal Pradesh, 259 blood samples were taken from people residing in various regions of the state and AmpF l STR® Identifiler® Plus PCR amplification kit was used for evaluation of 15 autosomal STR markers. A total of 149 alleles were investigated in this study with a mean allele number of 9.933 per locus. The locus D2S1338 was most informative in our data, as it had the highest discrimination power (PD-0.967) and the highest polymorphic information content (PIC-0.86). The matching probability and typical paternity index for all the studied loci were observed as 2.9x10 -18 and 4.7x10 5, respectively. Discrimination power (CPD) and exclusion power (CPE) for all the studied loci were observed as 1 and 0.999998.